Aspek Hukum Keselamatan Penumpang Transportasi Laut: Studi Empiris Di Pelabuhan Ketapang Banyuwangi - Mulyanto, Rudi; Sofyan, Mastiga; Putri, Etis Cahyaning (PMIH Untag Semarang, 2025)
Indonesia as an archipelagic country has a strategic role in the management of sea transportation to support national and economic connectivity. This study examines the protection and legal responsibility of ocean passengers based on Law No. 17 of 2008 concerning Shipping, with a focus on implementation at PT ASDP Indonesia Ferry (Persero) at Ketapang Port, Banyuwangi. This study uses an empirical legal method with an analytical descriptive approach, relying on primary data from interviews and secondary data from legal literature The results of the study show that PT ASDP has a legal responsibility in ensuring passenger safety, including the provision of infrastructure and accident insurance through PT Jasa Raharja. However, challenges are still faced in aspects of supervision, regulatory enforcement, and operational readiness. In conclusion, synergy between regulations, ship operators, and stakeholders is essential to improve safety and legal protection for sea transport passengers.